Prevalence and associated risk factors of violence against conflict-affected female adolescents: a multi-country, cross-sectional study. - Stark, Lindsay; Asghar, Khudejha; Yu, Gary; Bora, Caroline; Baysa, Asham Assazenew; Falb, Kathryn L. (Journal of Global Health, 2017)
Background: Over half of displaced civilians in humanitarian emergencies are children, and these settings pose unique threats to children's safety with long-lasting consequences. Our study broadens the limited evidence on violence against adolescent girls in emergencies by estimating prevalence and predictors of violence among adolescent girls aged 13-14 in South Kivu, Democratic Republic of the Congo (DRC), and aged 13-19 in refugee camps in the Benishangul-Gumuz region of Ethiopia.Methods: Survey data were collected from a sample of 1296 adolescent girls using Computer-Assisted Personal Interview and Audio Computer-Assisted Self-Interview programming. Predictors of violence were modeled using multivariable logistic regression.Results: The majority of adolescent girls (51.62%) reported experiencing at least one form of violence victimization in the previous 12 months: 31.78% reported being hit or beaten, 36.79% reported being screamed at loudly or aggressively, and 26.67% experienced unwanted sexual touching, forced sex, and/or sexual coercion. Across both countries, ever having a boyfriend and living with an intimate partner were strong predictors of violence. Fewer years of education completed in DRC, and young age in Ethiopia, were also associated with reported victimization.Conclusions: Prevalence of violence against adolescent girls is high in these two conflict-affected contexts. Findings indicate a need for programs targeting younger populations, broader efforts to address different forms of victimization, and increased recognition of intimate partners and caregivers as perpetrators of violence in conflict-affected settings.